VEGF165b and its mutant demonstrate immunomodulatory, not merely anti-angiogenic functions, in tumor-bearing mice. (June 2020) - Zhang, Huiyong; Xia, Wenjiao; Liang, Chen; Wang, Xiaoyin; Zhi, Lingtong; Guo, Changjiang; Niu, Zhiyuan; Zhu, Wuling
Highlights: Mutant VEGF165b were found to play immunomodulatory roles, beyond their anti-angiogenic functions. VEGF165b and Mutant VEGF165b was capable of inhibiting the proliferation of Tregs in vitro . Mutant VEGF165 was capable of inhibiting the accumulation of Tregs and MDSCs in spleen and tumors in tumor-bearing mice. Abstract: A great deal of evidence has shown that anti-angiogenic molecules and antibodies targeting the VEGF-A/VEGFRs signal pathway can also reverse tumor-induced immunosuppression to an extent. VEGF165b, an anti-angiogenic VEGF-A isoform, has demonstrated capacity as an efficacious anti-tumor therapy in mice as an anti-angiogenic agent. However, whether VEGF165b also plays an immunomodulatory role in anti-tumor field remains unclear. mVEGF165b effect on regulatory T cells (Tregs) in vitro were evaluated using flow cytometry and Cell Counting Kit-8 (CCK-8) methods. Its effects on Tregs (or Foxp3 expressing cells) and myeloid-derived suppressor cells (MDSCs) were analyzed in vivo using flow cytometry and immunostaining techniques. In this study, we found VEGF165b and its mutant (its half-life in plasma was extended 10 times while retaining its bioactivity; the VEGF165b mutant is called mVEGF165b for short) inhibited the proliferation of Tregs in vitro . In addition, mVEGF165b dramatically inhibited the accumulation of MDSCs and Tregs (or Foxp3 expressing cells) in the spleen and tumor in tumor-bearing mice. In conclusion, our findings demonstrated for the first time that VEGF165b and its mutant has immunoregulatory functions. It may be used as a potential immunomodulatory agent, beyond its anti-angiogenic capacities, in cancer therapies.